EKSISTENSI PERBANKAN SHARI’AH DALAM KONSTELASI PERBANKAN KONVENSIONAL DI INDONESIA - Dimyati, Dimyati; Budi Santoso, Muhammad Syafi'i (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2022)
This paper is aimed at describing about condition map of shari’ah banking among established conventional bankings. The shari’ah bank has now developed so quickly. This shows that the community interest toward the kind of bank is good. Positive response from community is based on the offered benefits such as variety of service given compared with conventional bank, there is no risk of negative spread, able to fasten growth and economic stability, and the tendency of the bank toward the weak community. However, shari’ah bank is like another financial institutions which have some risks and weaknesses. One of the weaknesses of shari’ah bank chieflyt is that it still “finds an ideal form”, realizing its existence is realively new. Some of its weaknesses can be seen from: liquidity aspect, owning interest oriented behaviors, inconsistent and unprofesional behaviors either management or community, there is no Islamic international bank and of course the lack of back up.